Analisis Kinerja dan Ergonomika Mesin Perajang Biomassa Tipe Slicer pada Pengolahan Batang Jagung - Ni’am, Ahmad Zydan; Asmara, Sandi; Amien, Elhamida Rezkia; Suharyatun, Siti (Jurnal Agricultural Biosystem Engineering, 2026)
Corn (Zea mays) production generates a significant amount of agricultural waste, particularly corn stalks, which are often underutilized and may cause environmental problems if not properly managed. This study aimed to evaluate the performance and ergonomics of a slicer-type biomass chopper in processing corn stalks. The experiment was arranged using a completely randomized factorial design with two factors: machine rotational speed (1500, 2000, and 2700 rpm) and the number of input stalks (4, 5, and 6 stalks), with three replications for each treatment. The observed parameters included working capacity, fuel consumption, specific fuel consumption, losses, and ergonomic aspects. The results showed that the treatments significantly affected all observed parameters. The highest working capacity was obtained at treatment R3M6 (791.2 kg/h), while the lowest fuel consumption and specific fuel consumption were found at R1M4. The lowest losses were observed at R2M6 (1.118%). Overall, treatment R3M6 demonstrated the best performance by providing a balance between high productivity and acceptable fuel efficiency. Ergonomic evaluation indicated that the machine could be operated adequately, although higher operational levels may increase operator workload. Therefore, the slicer-type biomass chopper has strong potential for improving the utilization of corn stalk waste in a more efficient and sustainable manner.